Kierunki i uwarunkowania polityki zagranicznej Jemenu w latach 1990-2014 - Bury, Jan (Polski Przegląd Stosunków Międzynarodowych, 2018)
Trends and determinants of Yemen’s foreign policy between 1990 and 2014 The article discusses the evolution of Yemeni foreign policy from the unification of the two Yemeni states till the aftermath of the events related to the so-called Arab Spring of 2011. It underlines the determinants and implications of Yemeni foreign policy, particularly in the economic context, as well as the external interventionism, which eventually led to the destabilization. The text also elaborated the Polish direction in Yemeni foreign policy at the turn of the 20th and 21st centuries.